APECED: is this a model for failure of T cell and B cell tolerance? - Kluger, Nicolas; Ranki, Annamari; Krohn, Kai (Frontiers in Immunology, 2012)
APECED and IPEX syndromes show similarities in the clinical presentations and immunological alterations, mainly regarding regulatory T-cells function. T-cell defect may lead to tissue destruction chiefly in endocrine organs. Besides, APECED is characterized by high-titer antibodies against a wide variety of cytokines, that could partly be responsible for the clinical symptoms during APECED, mainly chronic mucocutaneous candidiasis, and linked to antibodies against Th17 cells effector molecules, IL-17 and IL-22. On the other hand, the same antibodies, together with antibodies against type I interferons may be prevent from other immunological diseases, such as psoriasis and systemic lupus erythematous. The same effector Th17 cells, present in the lymphocytic infiltrate of target organs of APECED, could be responsible for the tissue destruction. Here again, the antibodies against the corresponding effector molecules, anti-IL-17 and anti-IL-22 could be protective. The occurrence of several effector mechanisms (CD4+ Th17 cell and CD8+ CTL and the effector cytokines IL-17 and IL-22), and simultaneous existence of regulatory mechanisms (CD4+ and CD8+ Treg and antibodies neutralizing the effect of the effector cytokines) may explain the polymorphism of APECED. Almost all the patients develop the characteristic manifestations of the complex, but temporal course and symptoms severity vary considerably, even among siblings. The autoantibody profile does not correlate with the clinical picture. One could speculate that a secondary homeostatic balance between the harmful effector mechanisms, and the favorable regulatory mechanisms, finally define both the extent and severity of the clinical condition in the AIRE defective individuals. The proposed hypothesis that in APECED, in addition to strong tissue destructive mechanisms, a controlling regulatory mechanism does exist, allow us to conclude that APECED could be treated, and even cured, with immunological manipulation.